The Role of Recycled Plastic Bottles in Enhancing Asphalt Longevity - Al-Tuwayyij, Husham; Al-Mukaram, Noorance; Ali, Atheer M. (Salehan Institute of Higher Education, 2025)
Producing “green” pavement is important in decreasing the negative effects of plastic on the environment and ensuring sustainable resource management. Because many worldwide strategies are aimed at reducing the use of plastic, this work studies a recycled polymer concrete modified by a defined amount of recycled plastic waste in asphalt. The specimens were prepared with a maximum optimal asphalt content using ±0.5% of the optimum level. The logic indicated that 11% plastic waste can be used as an alternative to the coarse aggregate. Experimental tests were carried out to examine moisture damage, short- and long-term aging, and compressive strength (rutting resistance). The measured properties were ITS, resilient modulus, and permanent deformation of the first load cycle and after 1200 load cycles using the PRLS device. In aging experiments, the resilient modulus was found to increase by 118% during the first cycle and by 40% after 1200 cycles. The decrease in permanent deformation was 40% and 48.5% after the first load cycle and after 1200 cycles, respectively. The results obtained in the moisture susceptibility test were within the required limit. Finally, the compressive strength of samples with asphalt content of 4.0%, 4.5%, and 5% was found to be 3660, 4120, and 2900 kPa, respectively. This achievement indicates the advantages of utilizing plastic waste in road construction to develop sustainable asphalt concrete with improved mechanical properties and reduced environmental impact, especially in hot climates such as Iraq, where it would be beneficial for rutting-sensitive roads.